Analisis Efektifitas Pencairan Dana Pada di Pemerintah Daerah: Kajian Empiris di Provinsi Papua Barat - Emiliana Antonina Kadmaer (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2020)
This study intends to examine the importance of supervision, standard operating procedures (SOP) and quality of human resources on the effectiveness of funds disbursement in a local government. The researcher used the context and environment of the West Papua Province as a research case. The research used full samples by spreading questionnaires to all treasurer in charge of disbursing funds. The study analyzes data in a descriptive and quantitative with multiple regression tools. Our results explain that there is an influence of supervision, SOP and the quality of human resources on the effectiveness of funds disbursement. Such impacts occur partially and simultaneously